Caracterização imuno-histoquímica de infiltrado inflamatório em tumores mamários espontâneos caninos - Fernandes, Carla Cristiane (2012)
The objective was to assess the association between race and age of dogs witch the occurrence of malignant tumors; check correlation to the use of hormones as a contraceptive method, expression of pseudopregnancy, tumor size and presence of ulceration with histological malignant or benign type. Characterize the inflammatory infiltrate of breast tumors by means of molecular markers for T lymphocytes (CD3), B lymphocytes (IgG), macrophages (MAC 385 and CD68) and cells expressing MHC II (TAL IB5) using the technique of immunohistochemistry. Compare the inflammatory infiltrates present in benign and malignant tumors. To evaluate the influence of tumor size, presence of ulceration, use of hormones as a contraceptive method, histologic type of breast cancer on survival of dogs. We used 80 female dogs, suffering from breast cancer, consulted in Veterinary Hospital of Federal University of Uberlândia (UFU) between 03/2010 a 03/211. The method used of immunohistochemistry was biotin-streptavidin complex. Of the 80 tumors included in the study, 90% were classified as malignant and 10% as benign. And 45% of these were of bitches (SRD) and among bitches race, the most common were coocker, pinscher (10%) and poodle (7,5%). According to age, 19 dog had from two to eight years of age and 61 were female dogs that had more than eight years old. Among these bitches 76,25% had no history of administration of contraceptive hormones and 23,75% used contraception hormones. A pseudocyesis was observed in 24 dogs. Assessment of correlation between tumor size, and skin ulceration with malignancy or benignity, no statistical difference between these variables. The malignancies were predominant and the type of cancer more othen and among the benign mixed tumor was the most common. There is no statistical correlation between malignancy of the use of hormones, pseudopregnancy, tumor size and ulceration. Malignant tumors as well as benign do not present statistical difference in the frequency of inflammatory infiltrate, when used as markers of inflammation CD3, IgG, MAC 385, CD68 E TAL IB5. No influence of the presence of ulceration, use of hormone, or the occurrence of benign or malignant tumors on survival of dogs suffering from spontaneous mammary tumors. But the size of tumors influence the survival of bitches, and bitches with tumors of larger sizes have shorter survival.